Adapting wastewater infrastructure to the new EU directive: Modernization challenges and environmental benefits – Masovian Voivodship case study - Agnieszka Karczmarczyk; Agnieszka Bus; Grzegorz Kaczor (Desalination and Water Treatment, 2025)
In response to the insufficient ecological status of surface waters, the EU has introduced a new Urban Waste Water Treatment Directive, which, by extending the scope and introducing more stringent requirements for the quality of wastewater plant effluents, intends to help achieve the objectives of the Water Framework Directive. This paper aims to indicate what consequences the introduction of the new directive will have for the existing wastewater infrastructure in terms of the modernization of wastewater treatment plants serving more than 2000 p.e. and its environmental effect. The analysis was carried out for the Masovian Voivodeship, which covers 11.4 % of Poland’s area and 14.6 % of Poland’s population. In the voivodeship, 326 municipal wastewater treatment plants are operating, constituting 10 % of Poland’s total number of wastewater treatment plants. Data for the analysis were obtained from a review of 136 agglomeration resolutions published in the official journal of the Mazovian Voivodeship. Results showed that 49 % of treatment plants with a p.e. above 10,000 would require modernization to increase total phosphorus removal efficiency and 31 % concerning total nitrogen removal. The environmental effect of implementing the new directive on the scale of the Mazovian Voivodeship will reduce the load of phosphorus discharged into receivers by 22 % and nitrogen by 5 %.